A contrastive study of pragmatic and semantic features in typical and atypical comparative constructions across English, Chinese, Russian, and Turkmen: cognitive interpretations explored - Annamyradova, Annagul (Frontiers in Education, 2025)
This article presents a contrastive analysis that sheds light on the similarities and differences of comparative constructions in English, Chinese, Russian, and Turkmen, and the reasons behind them from a cognitive perspective. Specifically, based on the analysis of the massive online English, Chinese, and Russian corpora, namely the Corpus of Contemporary American English, the Russian National Corpus, the Center for Chinese Linguistics Corpus, and the self-built Turkmen corpus data, this study focuses on pragmatic and semantic features of typical and atypical comparatives, providing a comprehensive analysis of their resemblances and distinctions. The similarities are chiefly exhibited in the prominent usage of typical comparative constructions, the occurrence of comparative deletion, and atypical semantic features based on the typical ones. The differences mainly lie in the preference for typical synthetic or analytic forms and the distribution between concrete and abstract atypical forms, expression forms of degree semantics in typical comparatives, and semantic types of atypical comparatives. The cognitive interpretations for the similarities of the typical and atypical comparative constructions in the mentioned languages are mainly reflected in human cognition toward the comparatives. The cognitive interpretations for the differences are mainly manifested in the diverse levels of salience and specificity of construal modes in the context of comparison.